2017
DOI: 10.1111/ppl.12560
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the chloroplast plastoquinone pool in the Mehler reaction

Abstract: Light-dependent oxygen reduction in the photosynthetic electron transfer chain, i.e. the Mehler reaction, has been studied using isolated pea thylakoids. The role of the plastoquinone pool in the Mehler reaction was investigated in the presence of dinitrophenyl ether of 2-iodo-4-nitrothymol (DNP-INT), the inhibitor of plastohydroquinone oxidation by cytochrome b6/f complex. Oxygen reduction rate in the presence of DNP-INT was higher than in the absence of the inhibitor in low light at pH 6.5 and 7.6, showing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…To study the effect of O2· on the redox state of PQ‐pool it is necessary to provide the supply of O2· to the membrane, using the X‐XO system in close proximity to the membrane surface. These conditions were explored in our previous study , where it was in particular found, that the incubation of thylakoids for 24/48 h at 5 °C after isolation facilitated such contact, and ESR experiments with the SASL‐16 spin probe revealed that such incubation resulted in changes of thylakoid membrane surface. The thylakoids preserved approximately 80% of photosynthetic activity after 48 h followed the isolation.…”
Section: Methodsmentioning
confidence: 99%
“…To study the effect of O2· on the redox state of PQ‐pool it is necessary to provide the supply of O2· to the membrane, using the X‐XO system in close proximity to the membrane surface. These conditions were explored in our previous study , where it was in particular found, that the incubation of thylakoids for 24/48 h at 5 °C after isolation facilitated such contact, and ESR experiments with the SASL‐16 spin probe revealed that such incubation resulted in changes of thylakoid membrane surface. The thylakoids preserved approximately 80% of photosynthetic activity after 48 h followed the isolation.…”
Section: Methodsmentioning
confidence: 99%
“…in the stroma, saturated already in low light (Mubarakshina et al , Borisova‐Mubarakshina et al ). Based on these data and on the data presented in (Mubarakshina and Ivanov , Borisova‐Mubarakshina et al , Vetoshkina et al ) it was proposed that Reaction 1 (interaction of O 2 •− with PQH 2 ) was the leading reaction producing ‘the membrane H 2 O 2 ’ molecules for the long‐term acclimation of plants to high light conditions (Ivanov et al ). For this reaction, O 2 •− presumably is generated within the thylakoid membrane by phyllosemiquinone (PhQ •− ) of PSI (Kozuleva et al ).…”
Section: Involvement Of the Pq Pool In The Long‐term Acclimation To Hmentioning
confidence: 98%
“…Early experimental studies provided the indirect data of the antioxidant activity of the reduced PQ in term of scavenging of O 2 •– (Kruk et al , Ivanov et al , Vetoshkina et al ). Recently, the reaction of O 2 •− with PQH 2 molecules (Reaction 1) in the PQ pool of thylakoid membrane was demonstrated (Borisova‐Mubarakshina et al ).…”
Section: Antioxidant Activity Of the Pq Poolmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism of 1 O 2 generation in PSI is unknown but it has been demonstrated that 1 O 2 in PSII is generated by charge recombination reactions of the primary radical pair, yielding the triplet state of chlorophyll. In addition to electron transport reactions at and within the photosystems, the plastoquinone pool is a source of O 2 •− /H 2 O 2 (Vetoshkina et al ). While light‐dependent ROS production damages PSII and PSI either directly or via the release of reactive electrophile species (Roach et al ), ultra‐violet (UV) and eventually blue light may directly damage the Mn cluster of PSII and cause photoinhibition.…”
mentioning
confidence: 99%